Situation of primary health care activities in non-communicable diseases for people in Dap Thanh commune, Ba Che district, Quang Ninh province in 2019 - Ban, Nguyen Vu; Anh Tuan, Le; Duc Nhu, Dang; Duc Loi, Vu; Ngoc Ha, Vu; Tuan, Mac Dang; Thanh Trung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2, 2022)
Objectives : Describe the current status of village health care workers (VHWs) in non-communicable diseases (NCDs) with people in Dap Thanh commune, Ba Che district, Quang Ninh province in 2019. Subjects and methods: Direct interview with people in Dap Thanh commune, Ba Che district, Quang Ninh province: 151 people aged 18 and over. Information related to exposure to messages about NCD risk factors and primary health care activities of VHWs. Results : Most of the respondents heard about NCD risk factors messages in the past 30 days, from 56.3% (messages in physical inactivity), and 59.6% (notifications). on diet), 75.5% (messages on alcohol use) to 79.5% (messages for smoking). Radio / television is the most popular source of messages (between 91.8% and 95.8%) and the majority of people hear these messages from one source (from 77.1% to 80.9%). Most of the respondents said that there is no local village health worker (53.6%). Among localities with village health workers, the most common services provided were health communication and education (54.3%), while only 30% received NCD management services. These services are rated effective and moderate (6.6 - 7.7 points). Farmers who smoke and have diabetes are more likely to hear health messages than the rest of the population. Conclusion: The results show that the primary health care activities for non-communicable diseases of the people in the Dap Thanh commune are not really effective, the role of health workers as an official source of information has not yet promoted their tasks mine. VHWs are not fully involved in primary health care activities of the people. Efforts should be made to improve the capacity and participation of VHWs in health care activities, especially those NCDs managed by local VHWs.